ChemInform Abstract: Dearomatization of Electron‐Deficient Nitrogen Heterocycles via Cobalt‐Catalyzed Asymmetric Cyclopropanation. Issue 34 (4th August 2016) - Joshi‐Pangu, Amruta; Cohen, Ryan D.; Tudge, Matthew T.; Chen, Yonggang
Abstract: Various fused nitrogen containing heteroarenes, including electron‐deficient ones, are cyclopropanated in a highly diastereoselective and enantioselective manner.